Risk Identification of Green Hydrogen Supply Chain in Ammonia Industry in Indonesia using Delphi and TOPSIS Methods - Priatama, Ananda; Tobing, Sheila (UI Scholars Hub, 2026)
The development of green hydrogen in Indonesia, while promising for supporting industrial decarbonization, remains in its early stages and faces various challenges across technical, economic, and regulatory domains. This study aims to identify and prioritize the risks linked to green hydrogen supply chain in Indonesia, particularly for applications in the ammonia industry. A set of 49 potential risk factors was initially compiled through literature review and prior studies. The Delphi method was employed with a panel of experts to validate these risks, ultimately refining the list to 27 critical risk factors. Subsequently, the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) method was used to quantify and rank these risks based on expert assessments of likelihood and impact. The results indicate that the most significant risks include improper location of facilities, policy and regulation development, access to funding and financial constraints, climate change and renewable energy availability, and political instability. Compared to previous studies in developed countries where technological and infrastructure risks dominate, this study highlights the prominence of policy and governance-related risks in Indonesia. The findings provide critical insights for stakeholders to design targeted mitigation strategies and prioritize actions that will foster a more resilient and investable green hydrogen ecosystem for ammonia industry in the country.